The Impact of online short and motivational videos by ISIS on twitter towards the Saudi youth? - Zanuddin, Hasmah; Alyousef, Yazeed (Science Publishing Corporation, 2018)
Social Media tools especially Twitter and YouTube are helping ISIS spread their promulgation and philosophy to a great many online sympathizers over the world. For sure, the gathering has effectively been utilizing online networking destinations, for example, Twitter, Facebook and YouTube to enroll new would be individuals. This is being done through pictures and the spilling of fierce online viral recordings shot and professionally altered that are focusing on youthful and susceptible individuals. Depicting a glamorized and 'cool' picture, Isis contenders are starting to go about as the new demigods of worldwide digital jihad. The Internet in this way is turning into the virtual play area for fanatic perspectives to be strengthened and go about as a resound chamber. This examination dissected 100 distinctive Facebook pages and 50 Twitter client accounts which produced more than 2050 outcomes and helped the writer make a typology of seven key conduct attributes and inspirations. The discoveries in this examination affirmed the creator's unique speculation, i.e. online detest is being utilized by gatherings, for example, Isis for an assortment of reasons, for example, enlistment and publicity. In addition, this material is composed and controlled by Isis as a method for distributing and conveying key messages. While these activities may make the figment of wellbeing, physical obstructions may not be a match for ISIS's innovatively smart techniques. Utilizing online networking and scrambled informing applications is an approach to for all intents and purposes manage homegrown fear based oppressors that are a great many miles away. Training and guidance towards the right can restrict youth from getting influenced by such activities and this paper will work on finding such solutions for the Saudi Youth. To gather data and analysis, interviews will be used as the instrument for data collection and the focus will be on assessing the impact of motivational videos on youth through Twitter in Saudi Arabia.